2003
DOI: 10.1073/pnas.0836654100
|View full text |Cite
|
Sign up to set email alerts
|

Moth chemosensory protein exhibits drastic conformational changes and cooperativity on ligand binding

Abstract: Chemosensory proteins (CSPs) have been proposed to transport hydrophobic chemicals from air to olfactory or taste receptors. They have been isolated from several sensory organs of a wide range of insect species. The x-ray structure of CSPMbraA6, a 112-aa antennal protein from the moth Mamestra brassicae (Mbra), was shown to exhibit a novel type of ␣-helical fold. We have performed a structural and binding study of CSPMbraA6 to get some insights into its possible molecular function. Tryptophan fluorescence quen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
152
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(169 citation statements)
references
References 31 publications
12
152
0
Order By: Relevance
“…There are other chemosensory proteins implicated in insect olfaction including those typified by CSPMbraA6 from the moth Mamestra brassicae. These proteins share no sequence homology with the OBP family and have completely different structures 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…There are other chemosensory proteins implicated in insect olfaction including those typified by CSPMbraA6 from the moth Mamestra brassicae. These proteins share no sequence homology with the OBP family and have completely different structures 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…The positively selected sites at the cavity opening could possibly affect which chemicals are bound. It has also been suggested that conformational changes in CSPs would trigger recognition in ORs (Campanacci et al, 2003). We can thus speculate that the positively selected sites may also have a role in the interaction between CSPs and ORs.…”
Section: Two Groups Of Genes With Different Evolutionary Patternsmentioning
confidence: 99%
“…HsalCSP11 consists of six a-helices and has a cavity with several openings (Figure 3), like the M. brassicae CSP. Three residues in M. brassicae CSP (Y26, W81 and W94) were suggested to be crucial for binding substrates (Campanacci et al, 2003). These three residues are highly conserved in the ant sequences, two of them showing no variation and one (MbraCSP W94) being mutated only in two sequences.…”
Section: Selection In Ant Csp Genesmentioning
confidence: 99%
See 2 more Smart Citations